Spatializing Blackness : architectures of confinement and Black masculinity in Chicago - Shabazz, Rashad, 1976- (New Black studies series., 2015)
"This project traces how architectures of confinement, policing, surveillance, migration, and mass incarceration orient and imbue Black male bodies and gender performance with the stigmata of carceral punishment. As the northern city with the largest 20th century influx of southern Blacks, Chicago provides a powerful case study to understand how urban planning, architecture, crowded living quarters, surveillance, and policing function to regulate Black men's bodies. Rashad Shabazz makes an important contribution to the growing work on Black (bodily) geographies and the complex entanglements between the emergence of the US prison regime (and prison industrial complex) and the densely historical complexities of Black subjectivity formation. By first illustrating how Black men's geographies have been delineated throughout the twentieth century in Black Chicago in spaces such as interracial sex districts, cramped kitchenettes, segregated house project, and prisons, Shabazz is then able to analyze and generalize the impact this mapping has had on the formation of Black masculinity, Black cultural production, and Black men's health in Black spaces beyond Chicago. Shabazz employs various methods (history, sociology, and literary criticism), theories (poststructuralism and critical theory), and disciplines (human geography, critical race studies, gender studies, cultural studies, and epidemiology) to highlight the importance of the racialization of space, the role of containment in subordinating Black people, the politics of mobility under conditions of 'freedom, ' and to ultimately discuss how Black men resist spacial containment"--